Combating Ageism: How Successful Is Successful Aging?. (16th July 2015) - Calasanti, Toni
Abstract : Purpose: To explore the extent to which the successful aging discourse has accomplished Rowe and Kahn's (1998) goal of combating ageism by (a) eradicating the narrative of decline and burden, and highlighting the positive aspects of aging; and (b) emphasizing individuals' ability to age successfully. To investigate this, I first situate ageism in a framework of age relations. Design and Methods: Using a qualitative approach, I analyze data generated from semistructured, in-depth interviews conducted among a diverse sample of 19 middle-aged men and women. Respondents were asked about what successful aging means to them, as well as their perceptions of their own aging, and old age. Results: Respondents are familiar with the notion of successful aging, and they believe that they can and should achieve this. However, rather than easing ageism, they experience the mandate to age successfully as a source of tension as they simultaneously realize that it is outside their control. They express continued fears of aging; and they implicitly blame themselves or others who fail to age successfully. Their comments suggest that, rather than supplanting the discourse of decline, the successful aging narrative coexists with it. Implications: By not challenging the age relations that denigrate differences, the successful aging framework does not eliminate ageism and might even increase it.